Subsídios para o planejamento de redes de greenways: estudo de caso de Ribeirão Preto, SP - Zeoti, Gustavo Nogueira (2020)
Greenways are green, linear open spaces which serve multiple purposes, primarily ecological and cultural. Ecological corridors, linear parks, tree-lined paths in old railway rights-of-way, among others, can be classified as greenways. In a system of open spaces, they can have the function of connecting components (nodes) of the landscape, such as fragments of natural vegetation, waterbodies, parks, historical sites etc. Greenway networks can be formed when the focus of the planning is on the connections of the landscape components themselves. In the city of Ribeirão Preto, SP, Brazil, a landscape planning instrument called “Protective Measures for Fragments and Urban Parks” has been implemented since 2012. The instrument is applied to fragments of native natural vegetation in territories that are under urbanization process. Its purpose is environmental protection, based on the hierarchy of fragments according to their priority for environmental conservation. Depending on the relevance defined for each fragment, protection measures are applied, such as ecological and leisure corridors, enabling the formation of a greenway network. However, one of the gaps identified concerns the incorporation of the cultural function in urban planning. The objective of this research is to propose guidelines for the planning of greenway networks to increase the ecological and cultural connectivity of the landscape, with the case study of Ribeirão Preto. Specifically, the objective is to analyze the municipal instrument emphasizing its legal and administrative context, the hierarchy of fragments and the characteristics of environmental protection measures; identify its gaps and potentials for improvement; to propose guidelines for the development of a classification and inclusion of the municipal railway heritage in landscape planning; and to propose guidelines for the planning of networks with emphasis on cultural aspects of the landscape. Multiple methods, such as bibliographic research, document research and analysis, field research, systematization of data in a GIS environment, and classifications of the Ribeirão Preto railway heritage were employed with a qualitative approach. As a result, the following guidelines were proposed for the improvement of the landscape planning instrument: simplification of the instrument; improvement of the active mobility and recreational cultural connectivity in greenway networks, in territories undergoing urbanization processes; inclusion of the cultural heritage function in the greenway planning, specifically for railway heritage along railway rights-of-way. Guidelines were proposed for the classification and inclusion of railway cultural heritage in landscape planning and the formation of greenway networks, in representative scenarios, in three different territorial sections in the municipality. The importance and possibilities of connectivity and integration of ecological and cultural factors in landscape planning are expanded through a connected network of greenways.